MODEL KONSTRUK KEPERCAYAAN PASIEN RUMAH SAKIT PINDAD TUREN MALANG (Magister Manajemen Universitas Wisnuwardhana, 2023)
Abstract. The purpose of this study was to analyze the effect of service quality and image on patient satisfaction and trust. In addition, this study also analyzes the indirect effect of service quality and image on patient trust which is mediated by patient satisfaction. The population of this study was 855 patients at Pindad General Hospital, while the sample used was 130 inpatients at Pindad General Hospital Malang Malang. The data source used in this research is primary data and the method to be used in data collection is the questionnaire data collection method. Analysis of the data used in research using Path Analysis (Path Analysis). The results showed that service quality and image had a direct effect on patient satisfaction, service quality, and image had a direct effect on patient trust, patient satisfaction had a direct effect on patient trust, and patient satisfaction was able to mediate the effect between service quality and patient trust image. Suggestions from this study are that Pindad Malang General Hospital needs to have medical staff and employees who have the skills and proficiency in carrying out their duties, always give a good impression by providing services to patients according to medical service standards, always giving a good impression by providing services to patients according to with medical service standards, accepting underprivileged patients by providing health insurance and free social service programs for underprivileged people and conducting social programs through health education to the community.